Severity and management of postabortion complications among women in Zimbabwe, 2016: a cross-sectional study. Issue 2 (10th February 2018) - Madziyire, Mugove Gerald; Polis, Chelsea B; Riley, Taylor; Sully, Elizabeth A; Owolabi, Onikepe; Chipato, Tsungai
Abstract : Objectives: Abortion complications cause significant morbidity and mortality. We aimed to assess the severity and factors associated with abortion complications (induced or spontaneous), and the management of postabortion care (PAC) in Zimbabwe. Design: Prospective, facility-based 28 day survey among women seeking PAC and their providers. Setting: 127 facilities in Zimbabwe with the capacity to provide PAC, including all central and provincial hospitals, and a sample of primary health centres (30%), district/general/mission hospitals (52%), private (77%) and non-governmental organisation (NGO) (68%) facilities. Participants: 1002 women presenting with abortion complications during the study period. Main outcome measures: Severity of abortion complications and associated factors, delays in care seeking, and clinical management of complications. Results: Overall, 59% of women had complications classified as mild, 19% as moderate, 19% as severe, 3% as near miss and 0.2% died. A median of 47 hours elapsed between experiencing complication and receiving treatment; many delays were due to a lack of finances. Women who were rural, younger, not in union, less educated, at later gestational ages or who had more children were significantly more likely to have higher severity complications. Most women were treated by doctors (91%). The main management procedure used was dilatation and curettage/dilatation and evacuation (75%), while 12% had manual vacuum aspiration (MVA) or electrical vacuum aspiration and 11% were managed with misoprostol. At discharge, providers reported that 43% of women received modern contraception. Conclusion: Zimbabwean women experience considerable abortion-related morbidity, particularly young, rural or less educated women. Abortion-related morbidity and concomitant mortality could be reduced in Zimbabwe by liberalising the abortion law, providing PAC in primary health centres, and training nurses to use medical evacuation with misoprostol and MVA. Regular in-service training on PAC guidelines with follow-up audits are needed to ensure compliance and availability of equipment, supplies and trained staff.